2013
DOI: 10.1016/j.jvs.2012.11.071
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 and TLR4 mediate skeletal muscle recovery in a murine model of hindlimb ischemia

Abstract: Introduction We have previously shown that the danger signal High Mobility Group Box 1 (HMGB1) promotes angiogenesis when administered to ischemic muscle. HMGB1 signals through Toll-like receptor 4 (TLR4) as well as the receptor for advanced glycation end-products (RAGE). However, the actions of these receptors in ischemic injury and muscle recovery are not known. We hypothesize that TLR4 mediates tissue recovery and angiogenesis in response to ischemia. Methods Femoral artery ligation was performed in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 34 publications
(34 reference statements)
0
49
0
Order By: Relevance
“…Whereas most have focused on the identification and testing of proangiogenic compounds or cellular therapies, there has been much less emphasis on evaluating the role of modulating inflammation to improve tissue recovery from the ischemic insult. We and others have investigated the role of toll-like receptor (TLR) activation in promoting angiogenesis and muscle recovery in a murine model of hindlimb ischemia (7)(8)(9)(10)(11)(12)(13)(14). TLRs mediate innate immune responses to bacterial components, including gram-negative bacterial lipopolysaccharide (LPS) (TLR4) and gram-positive bacterial lipoproteins (TLR2) (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas most have focused on the identification and testing of proangiogenic compounds or cellular therapies, there has been much less emphasis on evaluating the role of modulating inflammation to improve tissue recovery from the ischemic insult. We and others have investigated the role of toll-like receptor (TLR) activation in promoting angiogenesis and muscle recovery in a murine model of hindlimb ischemia (7)(8)(9)(10)(11)(12)(13)(14). TLRs mediate innate immune responses to bacterial components, including gram-negative bacterial lipopolysaccharide (LPS) (TLR4) and gram-positive bacterial lipoproteins (TLR2) (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…TLRs also sense endogenously released damageassociated molecular patterns (DAMPS), such as high-mobility group box-1 (HMGB1) to initiate an immune response (19). We have previously demonstrated that HMGB1, TLR4 and TLR2 modulate inflammation and muscle recovery after ischemia (8)(9)(10). TLR2 knockout (TLR2KO) mice develop abnormal vasculature, possibly influencing the regenerative process, whereas TLR4KO mice exhibit a robust regenerative phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…In response to infection, the absence of TLR4 activation results in death because of septicemia, whereas excessive activation can lead to serious complications of dysregulated inflammation and further tissue damage. Similarly, repair of sterile tissue damage also requires a well-controlled innate immune response in diseases such as myocardial infarction, stroke, and peripheral artery disease (1)(2)(3). Therefore, tight control of TLR4 signaling is imperative for a balanced and effective immune response.…”
mentioning
confidence: 99%
“…Indeed, as a DAMP molecule, HMGB1 gets more and more attention as a proangiogenic factor that could modulate the function of these angiogenesis-related cells. Upregulation of HMGB1 has been reported in many angiogenesis-related conditions, including cancer [7], cornea neovascularization [14], PDR [15], wound-healing [16], and ischemiainduced angiogenesis [17]. Here, we describe recent progress on how HMGB1 regulates angiogenesis in physiological or pathological status and discuss the therapeutic potential of targeting HMGB1 in angiogenesis-related conditions.…”
Section: Introductionmentioning
confidence: 96%